Perceived Stress Among Healthcare Workers At Jeddah Airport During Hajj Season Compared To Normal Working Days (The Review of Diabetic Studies, 2025)
Background: The Hajj pilgrimage imposes significant operational demands on healthcare systems, potentially elevating stress levels among healthcare workers (HCWs).Objective: To assess perceived stress levels among HCWs at King Abdulaziz International Airport during the Hajj season compared to normal working days and to identify associated demographic and occupational factors.Methods: A cross-sectional study was conducted using the 10-item Perceived Stress Scale (PSS-10). Data were collected during Hajj and post-Hajj periods. Statistical analyses included Wilcoxon signed-rank tests and subgroup analyses using Mann–Whitney U and Kruskal–Wallis tests.Results: Among 184 participants, mean PSS-10 scores were significantly higher during Hajj (20.7 ± 6.3) compared to post-Hajj (16.5 ± 5.8, p < 0.001). Subgroup analyses revealed higher stress levels among females, nurses, diploma holders, external support staff, younger age groups, less experienced workers, and first-time Hajj participants.Conclusion: HCWs experience elevated stress during the Hajj season. Also, certain subgroups were more affected. Targeted interventions are recommended to mitigate stress and maintain healthcare service quality during mass gatherings.